Penyuluhan Ekonomi Kreatif Tentang Permodalan dan Strategi Pemasaran Pada UMKM Salsabila Kelurahan Sasa Ternate - Mohammad Kotib; Prince Charles Heston Runtunuwu (Prisani Cendekia, 2022)
Capital is a very important factor of production for the continuity of a business, both large and small. Often production is disrupted due to this capital production factor experiencing problems. As a result, distribution and consumption channels also experience problems. For this reason, it is necessary to have a third party who can assist in capital matters. One of the third parties that can provide capital is banking. However, the availability of banked capital funds cannot be accessed by entrepreneurs, especially people who have very small capital or MSMEs. For this reason, it is necessary to provide assistance and training to MSMEs in obtaining capital from third parties, especially banks. The method used in this PKM activity is a method of training and mentoring related to capital and marketing so that it can mobilize MSMEs in carrying out their activities. Besides MSME owners, Salsabila also provides training to the surrounding community who play an active role in the process or flow of the program stages and their supervision, starting from from the stage of socialization, planning, implementation, and preservation of activities by contributing energy, thoughts, or in material form. From the analysis of the situation and problems faced by the Partner (MSME Salsabila), it can be stated that it is healthy in terms of capital. The achievement target formulated by the PKM Team is that partners are able to provide a way out in providing capital through third parties. Meanwhile, the outputs of the PKM program include: Journal of Community Service, Video Documentation of activities (Youtube), and this activity will also be published in print and online media.